1982
DOI: 10.1177/001872678203500202
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Job Motivation and Satisfaction Among Female and Male Managers

Abstract: This study examines the influence of sex on satisfaction with job related factors, overall job satisfaction, attitudes toward various motivators, and overall job motivation among managers. Using a statistical analysis of survey data, the study identifies many significant differences between male and female managers'perceptions and attitudes. The article then compares the findings to previous research, presents some questions pertinent to policy formation, and suggests avenues for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
2
6

Year Published

1987
1987
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 18 publications
1
47
2
6
Order By: Relevance
“…In contrast, some studies found that men were more satisfied than their female counterparts (Hulin & Smith, 1964;Weaver, 1974;Forgionne & Peeters, 1982). The possible reason for different levels of job satisfaction reported for male and female employees may be due to their different types of expectations from the job.…”
Section: International Journal Of Research Studies In Education 73mentioning
confidence: 93%
“…In contrast, some studies found that men were more satisfied than their female counterparts (Hulin & Smith, 1964;Weaver, 1974;Forgionne & Peeters, 1982). The possible reason for different levels of job satisfaction reported for male and female employees may be due to their different types of expectations from the job.…”
Section: International Journal Of Research Studies In Education 73mentioning
confidence: 93%
“…Some studies found that women employees are more satisfied with their jobs than men employees but, the other studies on the gender issue prove the opposite (Weaver, 1974;Shaprio & Stern, 1975;Forgionne and Peters, 1982;Clark, 1997;Ward & Sloane, 1998). While discussing the gender aspect of job satisfaction, Cambell et al (1976) argued that there is a difference between the expectations of men and women regarding their jobs.…”
Section: Research Theorymentioning
confidence: 99%
“…In others, it was found that women, compared to men, were more satisfied with their job (Clark 1997;Wharton et. Al., 2000), while in some studies the results were the opposite (Forgionne & Peeters, 1982).…”
Section: Job Satisfaction and Gendermentioning
confidence: 92%